History of artistic anatomy teaching tools in western culture (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This article explores the history of artistic anatomical teaching tools in Western culture, from its establishment in Classical Greece to the present digital era. It specifically focuses on human anatomy and traces the most significant milestones in its development, such as the transition from the Greek ideal to the individuality of ancient Rome, the access to cadavers in Renaissance universities, the use of photography to understand anatomy in motion and the and the more recent creation of three-dimensional digital models.
Keywords: Anatomy; art; education; history; tools